North–South International Transport Corridor Project as a Factor for Possible Strengthening of Russia’s Foreign Economic Relations - A. G. Volodin; M. A. Volodina (Контуры глобальных трансформаций: политика, экономика, право, 2019)
The article discusses the main provisions and ideas of the project of the international transport corridor “North - South” (ITC). The main economic benefits of this project are highlighted, as well as the problems that arise during the implementation of this ambitious transport corridor. The important aspects of the creation of the railway transport network between the participating countries of the project are considered and analyzed. Authors identify the main advantages of such a corridor for the main organizers of this transport artery. There are various factors that impede the implementation of the project: geopolitical contradictions between countries, the lack of administrative and legal unification of all documents, economic differences between the participating countries of the project, and a different approach to solving infrastructure and transport and logistics problems are intertwined here.